2018
DOI: 10.1016/j.ctro.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-ray minibeam radiation therapy on clonogenic survival of glioma cells

Abstract: HighlightsFirst in vitro study performed in an X-ray SARRP for minibeam irradiations.At equal mean dose, the same tumor control can be obtained with standard and minibeam irradiations.This contradicts the established paradigms of the standard radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This study compared micro‐ and nanodosimetric characteristics of three innovative types of spatially fractionated RT: photon, electron and proton minibeam radiation therapy. xMBRT and pMBRT approaches have been the subject of several dosimetric and biological studies, and these have demonstrated very promising results as a treatment for radioresistant tumors. However, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This study compared micro‐ and nanodosimetric characteristics of three innovative types of spatially fractionated RT: photon, electron and proton minibeam radiation therapy. xMBRT and pMBRT approaches have been the subject of several dosimetric and biological studies, and these have demonstrated very promising results as a treatment for radioresistant tumors. However, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Calculating the mean cell survival within a unit cell on a percentage scale is therefore independent of the accuracy of the model within the high dose regions. Increased clonogenic cell survival results mainly from the low doses (< 10 Gy) in the valleys where the cell survival is high on a percentage scale and accurately described by the LQ-model as also proposed by Guardiola et al 44 . It needs to be mentioned, that the calculated clonogenic cell survival based on the LQ-model is used as a simple biologically weighted measure for spatially fractionated dose distributions, but precise biological consequences cannot be withdrawn from the data (more details are found in the discussion).…”
Section: Methodsmentioning
confidence: 76%
“…We demonstrated a more accessible method for applying MRT [ 15 ]. Recently, several groups have begun to employ comparable methods for physical, biological and preclinical studies, proving the high reproducibility of this approach [ 29 , 30 , 31 , 32 , 33 , 34 ]. Here, the evaluations of the treatment efficacy of MRT on the murine melanoma model confirmed our previous results.…”
Section: Discussionmentioning
confidence: 99%